New Approaches to Therapy of Helicobacter pylori Infection (by the Materials of the Maastricht Consensus-IV, Florence, 2010) - A. G. Evdokimova; L. V. Zhukolenko; V. V. Evdokimov (Антибиотики и Химиотерапия, 2020)
European recommendations for eradication of Helicobacter pylori are presented. The increase of the resistance to clarithromycin requires the necessity of rational use of quadritherapy as the first line treatment and sequential therapy including drugs active against the pathogen with low resistance. New treatment regiments for patients with allergy to penicillin are recommended.